Clinical experience with thalidomide in the management of severe oral and genital ulceration in conditions such as Behcet's disease: use of neurophysiological studies to detect thalidomide neuropathy. - Janet Gardner‐Medwin; Norbert J. Smith; Roy Powell (1994)
OBJECTIVE--To examine the efficacy, dose, and safety profile, including neurophysiological testing of thalidomide used in 59 patients (including 23 with Behçet9s disease) to treat severe oral or genital ulceration (OGU). METHODS--We identified prospectively subjects (including women of childbearing potential) who had persistent OGU over periods lasting one to 40 years and whose active ulceration was not controlled by other therapies. They were treated with thalidomide. Retrospectively, we identified the number of subjects with complete resolution of the ulcers at one and two months of thalidomide therapy, and the dose required to maintain that improvement in those individuals who relapsed after stopping thalidomide. The decrease from the baseline sensory nerve action potential (baseline SNAP) amplitude value (derived from median, radial and sural nerve SNAPs) at which the development of paraesthesiae was likely to occur was also determined. RESULTS--Complete resolution of the ulcers occurred in 81% of patients within one month of thalidomide therapy at doses of 200 mg/day. No further thalidomide was required by 20% of patients responding and in the remainder improvement was maintained with smaller doses (7-200 mg/day). Using an approximate 50% decrease from baseline SNAP as an indication to discontinue thalidomide, the incidence of symptomatic neuropathy was 13.5%. No patients with a decrease of less than 42% developed neuropathy, and a further 13.5% were asymptomatic with a decrease in SNAP between 42 and 69%. Other side effects were seen in 44% of patients. There were no pregnancies and no requirement for urgent pregnancy testing. CONCLUSIONS--Thalidomide provided a useful therapeutic option in severe oral and genital ulceration which had not responded to other therapies. The physician must remain vigilant to the continuing danger of axonal neuropathy and teratogenesis at all times during thalidomide therapy.